2019
DOI: 10.1002/acn3.746
|View full text |Cite
|
Sign up to set email alerts
|

Association of corneal nerve fiber measures with cognitive function in dementia

Abstract: Objectives Corneal confocal microscopy ( CCM ) is a noninvasive ophthalmic technique that identifies corneal nerve degeneration in a range of peripheral neuropathies and in patients with multiple sclerosis, Parkinson's disease, and amyotrophic lateral sclerosis. We sought to determine whether there is any association of corneal nerve fiber measures with cognitive function and functional independence in patients with MCI and dementia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
81
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 44 publications
5
81
0
4
Order By: Relevance
“…Corneal confocal microscopy (CCM) is a noninvasive ophthalmic imaging technique for rapid, high-resolution imaging of corneal nerves. This technique has identified axonal loss in diabetes [21][22][23], impaired glucose tolerance [24], other peripheral neuropathies [25,26], Parkinson's disease [27], amyotrophic lateral sclerosis [28], multiple sclerosis [29] and dementia [30]. More recently we have shown a significant loss of corneal nerves in patients with TIA [31] and acute ischemic stroke [32][33][34], which was associated with elevated triglycerides and HbA 1c .…”
Section: Introductionmentioning
confidence: 88%
“…Corneal confocal microscopy (CCM) is a noninvasive ophthalmic imaging technique for rapid, high-resolution imaging of corneal nerves. This technique has identified axonal loss in diabetes [21][22][23], impaired glucose tolerance [24], other peripheral neuropathies [25,26], Parkinson's disease [27], amyotrophic lateral sclerosis [28], multiple sclerosis [29] and dementia [30]. More recently we have shown a significant loss of corneal nerves in patients with TIA [31] and acute ischemic stroke [32][33][34], which was associated with elevated triglycerides and HbA 1c .…”
Section: Introductionmentioning
confidence: 88%
“…In this study, the left and right MTA scores could not distinguish subjects with NCI from MCI. (21) reported corneal nerve loss and reasonable diagnostic accuracy in a small cohort of subjects with MCI and dementia. In the present study with a greater number of participants we show improved diagnostic accuracy with an AUC (86% vs 73%), sensitivity (81% vs 70%) and speci city (81% vs 75%) for MCI and a comparable AUC (85% vs 86%) and sensitivity (79% vs 85%) but improved speci city (91% vs 75%) for dementia.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, we showed that reduced corneal nerve ber density was associated with ischemic lesions in patients with acute ischemic stroke after adjusting for age, diabetes, gender, dyslipidemia and smoking [14]. We have demonstrated signi cant corneal nerve loss in patients with MCI and dementia, which was associated with the severity of cognitive impairment and disability [17]. Moreover we have recently shown that the diagnostic accuracy of CCM was high and comparable with MRI based medial temporal lobe atrophy (MTA) rating for dementia but was superior in MCI [18].…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, corneal nerve loss has been associated with the presence of ischemic lesions in patients with acute ischemic stroke after adjusting for age, diabetes, gender, dyslipidemia and smoking [14]. We have also previously reported that patients with mild cognitive impairment (MCI) and dementia have signi cant corneal nerve loss which is associated with the severity of cognitive impairment and disability [17,18].…”
Section: Introductionmentioning
confidence: 98%